2022
DOI: 10.1177/00220345221130013
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Extracellular Vesicle Profiling in Drainage Fluid After Neck Dissection in OSCC

Abstract: Lymph node metastasis is related to poor prognosis in oral squamous cell carcinoma (OSCC), and few studies have explored the relevance of postoperative drainage fluid (PDF) in metastasis. Extracellular vesicles (EVs) are nanosized vesicles that can transfer oncogenic molecules to regulate tumorigenesis. However, the proteomic profile of postoperative drainage fluid–derived EVs (PDF-EVs) in OSCC has not been elucidated. Herein, we collected drainage fluid from OSCC patients after neck dissection to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In recent years, the role of EHD2 in various types of carcinoma has attracted considerable attention. Studies have indicated that EHD2 may function differently depending on the type of cancer, serving as either a tumor suppressor 82 or an oncogene 83 involved in tumor progression and metastasis. On the one hand, this may be due to the different effects of EHD2 on different tissues.…”
Section: The Potential Clinical Applications Of Ehd2mentioning
confidence: 99%
“…In recent years, the role of EHD2 in various types of carcinoma has attracted considerable attention. Studies have indicated that EHD2 may function differently depending on the type of cancer, serving as either a tumor suppressor 82 or an oncogene 83 involved in tumor progression and metastasis. On the one hand, this may be due to the different effects of EHD2 on different tissues.…”
Section: The Potential Clinical Applications Of Ehd2mentioning
confidence: 99%
“…Drainage fluid enters lymph circulation through lymphatic vessels, playing an important role in immunity [64]. Wang et al, found 313 differential protein expression in drainage fluid-derived exosomes isolated from OSCC patients with or without lymph node metastasis by performing a proteome quantitative analysis [55]. They suggested drainage fluid-derived exosomes may serve as a potential metastasis marker for OSCC.…”
Section: Exosomes Derived From Other Originsmentioning
confidence: 99%
“…This discovery has paved the new way for studying the relationship between EVs and LNM in OSCC through postoperative drainage fluid. 107 However, there is still a long way to go for the clinical translation of these laboratory findings. Single-cell RNA sequencing (scRNA-seq) and tissue microarray have proven beneficial for better understanding the heterogeneity and connections between metastatic lymph nodes and primary OSCC.…”
Section: Research On Lnmmentioning
confidence: 99%
“…Our team's recent research confirmed the enrichment of EVs in the postoperative drainage fluid of OSCC patients and discovered two metabolic proteins, EHD2 and CAVIN1, to be strongly correlated with LNM. This discovery has paved the new way for studying the relationship between EVs and LNM in OSCC through postoperative drainage fluid 107 . However, there is still a long way to go for the clinical translation of these laboratory findings.…”
Section: Dilemmas and Prospectsmentioning
confidence: 99%